2007
DOI: 10.1016/s0929-6646(09)60213-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Infection due to Cryptosporidium Species Among Taiwanese Patients with Human Immunodeficiency Virus Infection

Abstract: Our findings indicate that the prevalence of intestinal colonization due to Cryptosporidium is low among HIV-infected patients in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
5
17
0
Order By: Relevance
“…bieneusi, respectively (7,19,22,24,26,(36)(37)(38)(39). The infection rate of Cryptosporidium in this study was similar to that in HAART-receiving HIV-positive patients in Taiwan (1.2% in 332 patients) (40) and Denmark (1.0% in 96 patients) (41), as well as in Brazilian patients in the HAART era (0.3%) (42). A previous study also showed that infection rates of Cryptosporidium decreased significantly in patients after the initiation of HAART in Brazil: 8.1% in 482 pretreated patients and none in 100 posttreated patients (43).…”
Section: Discussionsupporting
confidence: 75%
“…bieneusi, respectively (7,19,22,24,26,(36)(37)(38)(39). The infection rate of Cryptosporidium in this study was similar to that in HAART-receiving HIV-positive patients in Taiwan (1.2% in 332 patients) (40) and Denmark (1.0% in 96 patients) (41), as well as in Brazilian patients in the HAART era (0.3%) (42). A previous study also showed that infection rates of Cryptosporidium decreased significantly in patients after the initiation of HAART in Brazil: 8.1% in 482 pretreated patients and none in 100 posttreated patients (43).…”
Section: Discussionsupporting
confidence: 75%
“…A comparatively large proportion of participants infected with C. meleagridis was observed in a wide community in Haiti [69], a finding that was also reported at a high frequency in HIV-infected adults in Perù [74]. This species has been reported, even if rarely, by other studies regarding either children or adults with or without HIV infection from other geographical places as Portugal [75], India [36, 57], Taiwan [76], or Iran [77]. …”
Section: Introductionmentioning
confidence: 89%
“…Reports on the prevalence of cryptosporidial diarrhoea in HIV-infected adults from different parts of India from the mid-1990s have shown a range from 0.7 to 83% in symptomatic and from 1.4 to 57% in asymptomatic individuals, with very high rates in both groups and a strong correlation between immune status impairment and diversity of symptoms [235, 236]. In Taiwan the extremely low prevalence of intestinal cryptosporidiosis among HIV patients [76], despite detection of cryptosporidia in most of the surface waters [168], may be the result of using boiling water [5, 76]. In Malaysia, the commonness of fecal wastes from human and nonhuman hosts suggests that many environments, particularly water and soil, act as vehicles for the spreading of the disease [237].…”
Section: Cryptosporidiosis In Hiv-infected Individualsmentioning
confidence: 99%
“…19,20 Where studied, no differences in illness among adults have been noted between C. meleagridis and C. parvum or C. hominis . However, in HIV-positive children, infections with C. meleagridis were more likely to cause diarrhea than infection with C. parvum or C. hominis .…”
Section: Introductionmentioning
confidence: 91%